The relationship between iron and Ilmenite for photocatalyst degradation - Lee, Ru Bin; Lee, Kian Mun; Lai, Chin Wei; Pan, Guan Ting; Yang, Thomas Chung Kuang; Juan, Joon Ching (Elsevier, 2018)
Photocatalytic degradation of organic compounds is a key target for the development of sustainable environmental pollution management system. The use of pre-treated Ilmenite with low concentration of Fe ions via single step of chloride process is essential to generate a highly effective photocatalyst. In the present study, comprehensive investigations on Fe concentrations in Ilmenite has been conducted. Based on the findings, pre-treated Ilmenite with low Fe content (0.76–7.15 at%) was successfully synthesized through a single step chloride process by using 15–35 v/v% of HCl. Interestingly, Ilmenite with 1.62 at% Fe after pre-treated with 25 v/v% HCl was able to photodegrade 100% of the Reactive Black 5 (RB5) under visible light within 30 min. The improvement of photocatalytic degradation efficiency of the pre-treated Ilmenite is mainly attributed to the better photo-induced charge carrier mobility and low recombination losses.